Acquisition of English Grammatical Morphology by Native Mandarin-Speaking Children and Adolescents: Age-Related Differences. - Jia, Gisela; Fuse, Akiko (Journal of Speech, Language & Hearing Research, 2007)
Purpose: This 5-year longitudinal study investigated the acquisition of 6 English grammatical morphemes (i.e., regulaamzr and irregular past tense, 3rd person singular, progressive aspect -ing, copula BE, and auxiliary DO) by 10 native Mandarin-speaking children and adolescents in the United States (arrived in the United States between 5 and 16 years of age). The goals were fo chart and compare the acquisition trajectories and levels of mastery across the morphemes, identify when age-related differences emerged and which forms they took. Method: Morphological proficiency was measured by the accuracy of these morphemes in obligatory contexts during spontaneous speech. Results: The morphemes were mastered by different numbers of participants and showed different growth trajectories. Performance variance was partially predicted by age of arrival (AoAr) in the United States, with early arrivals achieving greater proficiency than late arrivals. However, such AoAr effects took several years to occur and only existed for 2 of the 6 morphemes (i.e., 3rd person singular and regular past tense). Growth curve analysis revealed that language environment was a stronger predictor of individual differences than AoAr. Results did not uncover age-related differences in the acquisition of tense versus non-tense-relafed morphemes, nor in regular versus irregular morphemes, nor in the error types. Conclusion: Findings support an Environmental account for age-related differences in 2nd language (L2) morphological acquisition. Results also indicate that the acquisition of some grammatical morphemes by school-aged immigrants takes several years to complete. As L2 learners exhibit some error types and difficulties similar to monolingual children with specific language impairment, caution needs to be taken when interpreting and using morphological errors as indicators of speech/language learning problems in this population. Reprinted by permission of the publisher.